Kajian Keandalan Pola Penanggulangan Sampah Padat. (Studi kasus Pada kota Balikpapan - Kalimantan Timur) - Lenora Leuhery (ARIKA, 2011)
Trash is a problem that needs to be managed properly, because if not, will have an impact and a significant risk to human life both in terms of aesthetics but especially in terms of health. So the quality of management that will be performed to determine the quality / environmental health degree there. This study was aimed to analyze the reliability of various systems associated with handling and processing of solid waste in the city of Balikpapan. System reliability analysis performed on dry and wet garbage container, garbage collection system (wagon wheels 2), TPS systems and Container and waste transportation system from TPS to TPA. The results showed that the reliability of the pattern of waste management in the city of Balikpapan in general is Andal (safe).